Medicine ball training implications for rotational power sports - Earp, J. E.; Kraemer, W. J. (Strength and Conditioning Journal, 2010)
Medicine ball exercises can be an important tool in the development of musculature that is important for sports performance. Medicine ball exercises can achieve angular specifity and stimulate tissues that may not be activiated inm exercise movements used in typical strength and conditioning programs. Medicine ball training allows complex sport-specific movements to be performed explosively with greater resistance than that seen during regular sports competition. Sports-specific development of high-velocity power movements can be achieved to help traing the sport-specific movements at higher power outputs on the force-velocity continuum.